Sociolinguistics and the Counselling Process - Conville, Richard L.; Ivey, Allen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
Sociolinguistics is the study of language as part of culture and society.Counselling, basically a linguistic-communicative process, has too often failed to consider systematic knowledge from related fields. This article discusses basic concepts of sociolinguistics and considers their relation to the counselling process. La socio-linguistique étudie la langue dans le cadre de la culture et de la société. La consultation, qui a à sa base un processus linguistique et communicatif, a trop souvent ignoré les données systématiques dedisciplines connexes. Cet article veut discuter les concepts de base de la socio-linguistique et indiquer leur lien au processus de la consultation.